Transanal Excision for early rectal cancer: An effective approach for selected patients - Nikolić, Marija; Trifunovic, Nemanja; Jašarović, Damir; Abazović, Tanja; Radivojević, Milica; Mitrović, Nebojša (Medical Gazzette, 2026)
Introduction: Transanal excision (TAE) is a rectum-preserving procedure for early-stage colorectal cancers in the lower and mid rectum. While total mesorectal excision (TME) remains the gold standard for rectal cancer, TAE is considered a viable alternative for selected patients. In cases where clinical and MRI findings suggest malignancy, and yet repeated biopsies show benign lesion, TAE could be both diagnostic and therapeutic procedure. Case Report: Three patients were evaluated for symptoms including the presence of blood and mucus in the stool and defecation difficulties. Clinical examination revealed tumor formations in the distal rectum, located no more than 4 cm from the anocutaneus line. Biopsy results confirmed the presence of tubulovillosus adenomas with high-grade dysplasia. Due to the tumor characteristics, irregular surface contours, firm consistency, and a wider base of tumor, malignancy was suspected prompting further diagnostic imaging. Pelvic MRI confirmed the suspected malignancy, leading to the decision to perform transanal excision in all patients. Histopathology confirmed early rectal adenocarcinoma with clear (R0) margins. The cases were reviewed by the Oncology board, recommending standard follow-up. Over 18 to 30 months, patients underwent regular monitoring with no recurrence or symptoms. Conclusion: Transanal excision is an effective, rectum-preserving procedure for selected patients with early rectal cancer or benign lesions. The reported cases demonstrate TAE’s success in achieving clear margins and favorable outcomes. Regular follow-up is crucial for detecting recurrences, and TAE remains a valuable alternative to more extensive surgeries in properly selected patients.